Die herkoms, intensie en metode van die "nuwe" Politieke Teologie van Johann Baptist Metz - Hofmeyr, Murray (HTS teologiese studies, 2002)
The genesis, intention and method of the “new” Political Theology of Johann Baptist MetzThis article describes J B Metz’s “transcendental phase”, when he worked on reformulating scholastic theology within the concepts of twentieth century anthropology. The major categories of Metz’s early thought are described in anticipation of the turn away from anthropology to the philosophy of history. The division of theological history into periods with the help of the categories anthropocentrism, theocentrism and cosmocentrism, and the distinction between conceptual framework and conceptual content, allow Metz to argue for the legitimacy of the modern era from a Christian (and specifically Catholic) point of view.